Exequatur in voluntary jurisdiction proceedings: public order and the triumph of the best interests of the child - Santaolalla Montoya, Cayetana (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Exequatur of a sentence of Conaky Republic of Guinea, where the parents renounce the parental authority of their daughter, so that, when it is recognized in Spain, her uncles, who live in Spain, exercise the guardianship over the girl who lives in Barcelona. In first instance, it is denied because it is considered contrary to the Spanish legal system that does not recognize the possibility of renouncing, on the part of the parents, their parental authority. For its part, the Provincial Court of Barcelona partially upheld the appeal and considers that it should be recognized as not being contrary to Spanish public order. Both in the first instance and in the appeal, the guardianship is not granted, but is recognized the guard with guardianship functions to the uncles of the minor who live in Spain.